Identifikasi jenis pohon riparian dan kualitas mata air di Kecamatan Amarasi Barat, Kabupaten Kupang - Manewalu, Agnes; Taloim, Netri; Belo, Joana Da Conceicao; Yeni, Yustina; Semiun, Chatarina Gradict (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
Riparian trees act as bioindicators and phytoremediators to maintain water quality. This research aimed at identifying riparian trees and water quality in several springs in West Amarasi sub-district. The method used in this research was Quadrat Sampling Technique which was carried out randomly. In each plot, researchers carried out plant identification. In addition, abiotic data were collected on water quality parameters (DO, TDS, water temperature, pH, conductivity, salinity, BOD, COD, TSS and Pb). Data analysis included the Shannon-Wiener diversity index and gap analysis between physical and chemical water parameter data and water quality criteria according to PP RI Number 22 of 2021 (Class I). The results found that Toobaun springs consisted of 18 types of riparian trees, 14 types of Nekbaun springs. Meanwhile, in Merbaun springs there were 7 types, with a diversity index ranging from very poor to moderate. Furthermore, water quality parameters that did not fulfill the water quality criteria include BOD, COD and Pb.